Electroacupuncture Stimulation Suppresses Postoperative Inflammatory Response and Hippocampal Neuronal Injury - Xiang-feng Wang; Qin Lin; Guan-hui Wang; Gen-ming Zhan; Wei Liu; Zhi-wei Lin (Mediators of Inflammation)
Postoperative cognitive dysfunction (POCD) is consequence of anesthesia and surgery that primarily affects older people. The prevention and treatment of POCD has drawn an increasing attention in recent decades. Here, we established the animal model mimicked POCD after femoral fracture surgery, and analyze the effect of acupuncture stimulation on postoperative cognitive function after femoral fracture surgery. Compared with the mock group, the cognitive function performance was significantly decreased both in the anaesthesia group and the surgery group, between which the symptoms were more severe in the surgery group. The peripheral inflammation response and the neuron impairment and inflammation response in the hippocampus were observed in the surgery group, but only peripheral inflammation response was detected in the anaesthesia group. These findings indicated the POCD was the synergistic outcome of anaesthesia and surgical stimulation but with different pathogenic mechanism. The surgery with mental tri-needles (surgery+MTN) group outperformed the surgery group in terms of cognitive function performance. The peripheral inflammation response and the neuron impairment and inflammation response in the hippocampus was significantly reduced by the electroacupuncture stimulation. Our findings indicated the protection of electroacupuncture form POCD after femoral fracture surgery is related to the inhibition of inflammation response and neuron impairment.